If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + 7 = -10x Reorder the terms: 7 + -4x = -10x Solving 7 + -4x = -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. 7 + -4x + 10x = -10x + 10x Combine like terms: -4x + 10x = 6x 7 + 6x = -10x + 10x Combine like terms: -10x + 10x = 0 7 + 6x = 0 Add '-7' to each side of the equation. 7 + -7 + 6x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 6x = 0 + -7 6x = 0 + -7 Combine like terms: 0 + -7 = -7 6x = -7 Divide each side by '6'. x = -1.166666667 Simplifying x = -1.166666667
| 23=-8x-7+2x | | 7(a+2)-5=7a+9 | | 6k+7=43 | | 2(x+3)=3(2x-10) | | -11x-8+3x=24 | | 2(-7x+6)=-16-7x | | 5.9x=-30.09 | | -5=7+4x | | 2c+3=4(5c-6) | | 4(2x+3)+5=1 | | -5x-4(-7-4x)=36+7x | | 60=4(5-x) | | 2(5+x)=-30 | | x-21=-x*2 | | 3(7x-7)=-6+6x | | 4x-148=3x+566 | | 50+0.9*(y-30)+10+10+28=y | | 5[2-3(x-8)]=26-8x | | (2x^4)+16x=0 | | 2x+(-4x)=22 | | 4x+9-49=0 | | -1+3(v-7)=-28 | | 2x^2+22x+60=x | | 20y+13=15y-8 | | 4x+4x=64 | | (18a^3)-72a=0 | | z-0.45=5.97 | | 3a+(4b+2)I=9-6I | | 50+0.9*(y-30)=y | | -5x+24=-8(x-6)+6x | | -(-a)= | | 3x(4)=2 |